L1 retrotransposons exploit RNA m6A modification as an evolutionary driving force - Sung-Yeon Hwang (Nature Portfolio, 2021)
L1 is a group of active retrotransposons in humans. Here the authors show that m6A modifications on L1 RNA increase translation efficiency and retrotransposition in human cells. M6A motifs are more enriched in evolutionary young L1s.